South African Space(s) and Belonging(s). A critical analysis of Max Annas’ thriller Die Mauer in consideration of teaching German as a Foreign Language (GFL) within South African Tertiary Education. - Crous, Mikhaila (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018